A metástase do bem: a odisséia pessoal de professoras resilientes e sua influência na comunidade escolar - Assis, Eliasaf [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The complex plot that lies behind contemporary social life seems to point to a scenario of acute perplexity. When an individual experiences a kind of intellectual and emotional diaspora and is therefore under a process of depersonalization and unable to resist morally the aegis of the market, he panics and, like the subject of one of the most famous paintings of Edvard Munch, he cries out for direction. Seeking to build a theoretical model for perplexed people of this new reality to find ways of coping and overcoming, such as at the time of Maimonides, this study, in first place, seeks to relate the theory of moral development of Lawrence Kohlberg, the triadic model of resilience and, such as observed in aprevious research (ASSIS, 2009), the significant experiences, that are permeated with epiphanies, of relationships with moral mentors. The synthesis we got was this: the resilience and moral development operations are tributaries of significant experiences of personhood linked to relationships with mentors. This synthesis was used as a working hypothesis and guided a empirical research that described life trajectories of five municipal teachers of São Paulo, who were chosen by some of their fellow teachers because of their stories of resilience, their examples of excellence in work and their influence on the community where they work. Throughout the narratives we compare these personal stories of overcoming with the triadic model of resilience and we verify that significant experiences of personhood and relationships of moral mentoring are present in these stories as factors that influenced them. We also observe that these factors influenced, along with the experience of resilience, the training process and the formation of the professional identity of teachers and are present in their performance in the school community

A trama complexa que recobre a vida social contemporânea parece apontar para um cenário de aguda perplexidade. Ao experimentar uma espécie de diáspora intelectual e afetiva, portanto sob um processo de despersonalização e sem condições de opor resistência à égide do mercado, o indivíduo se desespera e, tal como o sujeito da tela mais conhecida de Edvard Munch, grita por sentido. Visando à construção de um modelo teórico para que os perplexos desta nova realidade, a exemplo dos da época de Maimônides, encontrem caminhos de enfrentamento e superação, este estudo, em primeiro lugar, buscou aproximar e relacionar a teoria do desenvolvimento moral de Lawrence Kohlberg, o modelo triádico de resiliência e, tais como observadas em pesquisa anterior (ASSIS, 2009), as vivências significativas, permeadas de epifanias, próprias dos relacionamentos com mentores morais. A síntese a que se chegou foi a seguinte: as operações de resiliência e o desenvolvimento moral são tributários de experiências significativas de pessoalidade vinculadas a relacionamentos com mentores. Assumida como uma hipótese de trabalho, essa síntese orientou uma investigação empírica que retratou trajetórias de vida de cinco professoras de educação infantil e básica da rede municipal de ensino da cidade de São Paulo, indicadas por alguns de seus pares em razão de possuírem histórias pessoais de resiliência, influenciarem positivamente a comunidade em que atuam e serem exemplos de excelência no trabalho. Os relatos permitiram comparar essas histórias pessoais de superação com o modelo triádico de resiliência e verificar que nelas estão presentes e estreitamente relacionados, como fatores influenciadores, vivências significativas de pessoalidade e relacionamentos de mentoreamento moral. Observou-se, também, que esses fatores, juntamente com as experiências de resiliência, influenciaram, por sua vez, o processo de formação e a...
Keywords: Ética; Desenvolvimento moral; Professores; Resiliencia (Traço da personalidade); Ethics